(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This study developed a pain evaluation scale and validated it for the Portuguese language. Development of the inventory - 308 readily available pain descriptors - were searched in international literature and validated by six judges. One hundred descriptors of acute pain and 100 descriptors of chronic pain were found, which were used in the next stage. Statistical validation - 493 health professionals and 146 patients experiencing acute and chronic pain participated in the study. Instructions, pain descriptors and respective definitions, pen and measuring tape were provided to participants. Psychophysical methods were used to establish categories, magnitude and cross-modality matching using line-length. Results revealed the ranking of the most frequently used descriptors of acute and chronic pain, with power equal to 0.99, close to the predicted (one), using line-length estimations. The Multidimensional Pain Evaluation Scale is thus validated for the Portuguese language.